Calcium Oxide from Limestone as Solid Base Catalyst in Transesterification of Reutealis trisperma Oil - Suprapto Suprapto; Tikha Reskiani Fauziah; Meiske S Sangi; Titie Prapti Oetami; Imroatul Qoniah; Didik Prasetyoko (Universitas Gadjah Mada, 2016)
CaO catalysts were synthesized from limestone by thermal decomposition and coprecipitation methods. The CaO and MgO reference catalysts were also synthesized for comparison. The catalysts were characterized by X-ray diffractometer (XRD) and the analysis result was refined by Rietica software. CaO catalyst obtained by coprecipitation method has higher purity of CaO and lower MgO content than those of calcined CaO. The catalysts were also characterized by Fourier Transform Infrared (FTIR) spectroscopy. FTIR spectra showed that the catalysts can be easily hydrated and carbonated in air. The catalytic activity of the catalyst was studied in transesterification reaction of Reutealis trisperma (Kemiri Sunan) oil with methanol. Transesterification reaction was carried out at oil to methanol molar ratio 1:1 and 1% of catalyst at 60 °C for 2 h. Catalytic activity of CaO catalyst obtained by coprecipitation was higher than calcined CaO. The methyl ester yield obtained from synthesized CaO, CaO from coprecipitation, calcined CaO, and synthesized MgO catalysts were 56.13; 37.74; 15.97; and 3.61%, respectively.